Researching in definition of maritime piracy - Villanueva Turnes, Alejandro (2023)
The main objective of this research is to try to understand the root of the actual maritime piracy’s definition, this research will analyze the actual most relevant aspects and doctrinal opinions. At the same time it will discuss about it’s regulation in the United Nations Convention on the Law of the Sea of 1982 and in the Convention for the Suppression of Unlawful Acts against the Safety of Maritime, followed by a special mention about the Spanish regulation, because this country have suffered not so long ago this kind of activities. In the course of the investigation it will be concluded that there is a need of an update of the maritime piracy definition and their rules, as the piracy is still a real threat nowadays.